The ludic, the aesthetic and the poetic universe in Music Education: some thoughts after Edgar Morin - Cardoso, Renato [UNESP] (Programa Pos-graduacao Musica-ppgm, 2017)
Edgar Morin surrounds the theme of human identity on his book The Method vol.5 - the humanity of humanity. In this work, the author develops what he calls the dialogic of sapiens-demens, by taking the human identity as a continuum between its empirical/technical/rational aspect and its symbolic/mythologic/magic aspect. Beyond these superlatives, the author theorizes about three states that set up the human universe: the ludic, the aesthetic and the poetic. Therefore, theses states are the gateway to music and music education thinking, as an open and processual form, grounded in artistic and musical scope. The ludic-aesthetic-poetic universe is, in its essence, the manifestation of the living poetry, the utter state of meaning-making. The concepts of ludic, aesthetic and poetic, while they set out the field of music making, they also act as an opening towards transversal themes and knowledge connection necessary to the currents needs of our culture.
Keywords: Sapiens-demens; Aesthetic state; Complexity; Music education